ESLAV/ECLAM/LAVA/EVERI recommendations for the roles, responsibilities and training of the laboratory animal veterinarian and the designated veterinarian under Directive 2010/63/EU. (April 2015) - Poirier, G M; Bergmann, C; Denais-Lalieve, D G; Dontas, I A; Dudoignon, N; Ehall, H; Fentener van Vlissingen, J M; Fornasier, M; Kalman, R; Hansen, A; Schueller, S; Vergara, P; et al.
Directive 2010/63/EU was adopted in September 2010 by the European Parliament and Council, and became effective in January 2013. It replaces Directive 86/609/EEC and introduces new requirements for the protection of animals used for scientific purposes. In particular, it requires that establishments that breed, supply or use laboratory animals have a designated veterinarian (DV) with expertise in laboratory animal medicine, or a suitably qualified expert where more appropriate, charged with advisory duties in relation to the well-being and treatment of the animals. This paper is a report of an ESLAV/ECLAM/LAVA/EVERI working group that provides professional guidance on the role and postgraduate training of laboratory animal veterinarians (LAVs), who may be working as DVs under Directive 2010/63/EU. It is also aimed at advising employers, regulators and other persons working under the Directive on the role of the DV. The role and responsibilities of the DV include the development, implementation and continuing review of an adequate programme for veterinary care at establishments breeding and/or using animals for scientific purposes. The programme should be tailored to the needs of the establishment and based on the Directive's requirements, other legislations, and current guidelines in laboratory animal medicine. Postgraduate laboratory animal veterinary training should include a basic task-specific training module for DVs to complement veterinary competences from graduation, and continuing professional development on the basis of a gap analysis. A tiered approach to further training in laboratory animal veterinary medicine and science offers career development pathways that are mutually beneficial to LAVs and establishments.